Adsorptive removal of Ni(ii) ions from aqueous solution and the synthesis of a Ni-doped ceramic: an efficient enzyme carrier exhibiting enhanced activity of immobilized lipase. Issue 69 (7th July 2016) - Qu, Yanning; Wu, Zhongjie; Huang, Renliang; Qi, Wei; Su, Rongxin; He, Zhimin
Abstract : We report the successful removal of Ni 2+ from aqueous solution via entrapment by chitosan nanoparticles, followed by calcination with a ceramic matrix to construct a novel carrier for lipase immobilization with enhanced activity. Abstract : We herein report a novel strategy for the removal of heavy metals and the subsequent preparation of a metal ceramic for immobilizing enzymes. To demonstrate this concept, Ni 2+ ions were removed from an aqueous solution via entrapment by chitosan nanoparticles, and the resulting Ni(ii )-containing precipitate was mixed with the ceramic matrix to give the Ni-doped ceramic (Ni-CP), which was subsequently applied in lipase immobilization. Under optimized conditions, Ni 2+ removal reached 99.4%, and the Ni-CP showed significant chelation towards lipase following immobilization. In addition, a lipase activity yield of 164% was obtained under optimal conditions. Furthermore, the thermal and storage stabilities of Ni-CP-lipase exhibited a wider applied range, and the Ni-CP reusability was maintained at 97.5% following 20 cycles, suggesting high stability and excellent recyclability. Hence, the entrapped Ni 2+ exhibited improved stability, thus reducing leakage into the environment. Furthermore, the chelation between Ni 2+ and lipase improved enzyme activity and stability, and thus, may be suitable for application in large-scale production. It is therefore expected that this novel approach for enzyme immobilization has the potential to serve as an important technique in the field of biocatalysis.